2007
DOI: 10.1111/j.1570-7458.2007.00569.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Napier grass (Pennisetum purpureum) varieties for use as trap plants for the management of African stemborer (Busseola fusca) in a push–pull strategy

Abstract: We evaluated eight Napier grass [Pennisetum purpureum Schumach (Poaceae)] varieties, used in various parts of eastern Africa as fodder, for their potential role as trap plants in the management of the African stemborer, Busseola fusca Füller (Lepidoptera: Noctuidae) through a push–pull strategy. Oviposition preference, larval orientation, settling, arrest and dispersal, feeding, mortality and survival, and development were determined for each of these varieties under laboratory and screen house conditions. Two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
67
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(74 citation statements)
references
References 43 publications
4
67
0
2
Order By: Relevance
“…Although Van den Berg et al (2006) and Khan et al (2007) showed that B. fusca moths did lay their eggs on Napier grass, the preference for the grass to maize was not strong and oviposition was largely similar on these two plant species. Attractiveness alone is, therefore, unlikely to have resulted in the efficacy of Napier grass as trap crop for B. fusca in this study.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Although Van den Berg et al (2006) and Khan et al (2007) showed that B. fusca moths did lay their eggs on Napier grass, the preference for the grass to maize was not strong and oviposition was largely similar on these two plant species. Attractiveness alone is, therefore, unlikely to have resulted in the efficacy of Napier grass as trap crop for B. fusca in this study.…”
Section: Discussionmentioning
confidence: 86%
“…Preferences for oviposition by B. fusca and C. partellus on Napier grass (Pennisetum purpureum Schumach) instead of maize plants under laboratory conditions have been reported by Van den Berg et al (2001), Khan et al (2006Khan et al ( , 2007, Van den Berg (2006a, 2006b and Mohamed et al (2004). Jindal et al (2012) reported attraction of Napier grass to C. partellus under semi-field conditions.…”
Section: Introductionmentioning
confidence: 82%
“…It was suggested that this system, developed initially for pest management in sub‐Saharan Africa, did not study short‐range interventions between plants and insects. However, in the papers (Khan et al ., , ), evidence is provided on the value of short‐range attractancy by the trap crop P. purpureum to the stemborer moths B. fusca and C. partellus . Eigenbrode et al .…”
Section: Success and Lessons From Exploiting Plant Volatile‐mediated mentioning
confidence: 99%
“…In crop land management systems, it is used as a mulch to control weed infestation and soil erosion [2] and as a trap plant in the push-pull strategy, a pest management practice which uses repellent intercrop 'push' plants and attractant trap 'pull' plants [23] for insect pest control in Africa, particularly for the maize stem borer [24,25]. Plants are also used to scavenge pollutants, such as heavy metals, and Napier grass has been used in phytoremediation strategies, for example for the cleanup of cadmium-affected soil, reducing the concentration of cadmium to a depth of 15 cm in soil [17].…”
Section: Economic Importancementioning
confidence: 99%